Development Framework for the Evaluation of Usability in E-Government: A Case Study of E-Finance Government of Malang - Lestari, Vivin Ayu; Aknuranda, Ismiarta; Ramdani, Fatwa (Journal of Information Technology and Computer Science, 2017)
E-government is an effort to utilize information and communication technology especially internet to improve public service quality which generally implemented in a web based application. Usability is one of the important quality criteria for the success of a web. In this study we developed a framework for evaluation of usability in e-government consisting ofÂ  eight stages: (1) determining the evaluation objectives, (2) determining the usability aspects, (3) determining the metrics usability, (4) selecting usability evaluation method candidates, (5) determining the required criteria of the method to be evaluated, (6) evaluating the method, (7) selecting and making the instrument, and (8) evaluate usability.. The results of the application of this framework in the case study of e-finance resulted in two methods used: user testing and questionnaires. The evaluation of usability in e-government for e-finance case studies using the proposed framework results in usability level of e-finance in terms of effectiveness, efficiency, and user satisfaction are 96%, 92%, and 70 respectively. Which can be identified to be grouped into 16 problems consisting of aspects of effectiveness and efficiency.